2019
DOI: 10.1097/md.0000000000017301
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of lymphovascular space invasion in patients with early stage cervical cancer in Jilin, China

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
3
17
1
Order By: Relevance
“…However, the authors argue to take into account LVSI in this decision, as its presence is associated with LNMan association which has been demonstrated previously [9,11,12]. In a review by van Meurs et al on 535 patients with stage IA2 cervical cancer [9], tumours with LVSI were observed with a 12.0% LNM rate, versus 9.3% in our study.…”
Section: Discussionsupporting
confidence: 56%
“…However, the authors argue to take into account LVSI in this decision, as its presence is associated with LNMan association which has been demonstrated previously [9,11,12]. In a review by van Meurs et al on 535 patients with stage IA2 cervical cancer [9], tumours with LVSI were observed with a 12.0% LNM rate, versus 9.3% in our study.…”
Section: Discussionsupporting
confidence: 56%
“…Yan et al [ 29 ] also demonstrated an improved prognosis for the survival of IB1-IIB stage cervical cancer patients with high-risk factors or more than two intermediate-risk factors undergoing adjuvant CCRT therapy. However, patients with intermediate-risk factors do not benefit from a standardized treatment regimen, which requires therapy management under the experience of clinicians [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, in our study, it would be more likely that LVSI is associated with a higher risk of lymph node metastases, regardless of LRH or ORH. There are studies 23–27 indicating that LVSI, together with other pathological characteristics such as tumor size, result in an increased risk of lymph node metastasis, that is one of the most important prognostic factors in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%